(untitled) (Bangladesh Journal of Pharmacology, 2015)
To evaluate the effectiveness and safety of adjuvant chemotherapy of megestrol acetate (MA) in advanced breast cancer, we searched CBM, CNKI, VIP, Wangfang Data and PubMed, and collected randomized controlled trials (RCT) of adjuvant chemotherapy of MA in advanced breast cancer. MA significantly increased treatment efficiency (p=0.0010); improve weight (p<0.0001), appetite (p=0.001) and KPS (p=0.06); ameliorate leucopenia (p=0.02), thrombocytopenia (p=0.02) and hemoglobin (p=0.01); reduce gastrointestinal reaction (p=0.0005) of the patients of adjuvant chemotherapy in advanced breast cancer. MA significantly increased treatment efficiency, improve the nutritional situation, reduce bone marrow suppression, and gastrointestinal reaction of the patients of adjuvant chemotherapy in advanced breast cancer. High-quality RCTs are needed to guidance for preliminary studies of the effective treatment of adjuvant chemotherapy of MA in advanced breast cancer.